PENGARUH PEMBERIAN PERAWATAN PAYUDARA DENGAN TEHNIK PIJAT OKETANI TERHADAP KELANCARAN PRODUKSI ASI PADA IBU POST PARTUM - Elvrinica Christina; Bela Purnama Dewi (Jurnal Kesehatan dan Pembangunan, 2026)
Coverage of exclusive breastfeeding for babies in the world is 41%, while the WHO target for exclusive breastfeeding in the world is 70% (Global Breast Feeding Collective, Unicef ??and WHO, 2018). Not all postpartum mothers immediately express breast milk. To stimulate the release of the hormones prolactin and oxytocin in Indonesia, there are many types of methods that can be used as an option for mothers who experience problems during breastfeeding, one of which is the oketani massage technique. This study aims to determine the effect of providing breast care using the oketani massage technique on breast milk production in post partum mothers at RSIA Az-Zahra Palembang. This research method uses a pre-experimental research method with a one group pretest—post test design. The sample in this study was 71 post partum mothers on days 1-3 using the purposive sampling method. The research was conducted from 1 - 31 January 2025 at RSIA Az-Zahra Palembang. The results of this research showed that based on the Wilcoxon test, it was found to be 0.001 < 0.05, it could be concluded that there was a significant effect of breast care using the oketani massage technique on the smoothness of breastfeeding in postpartum mothers at RSIA Az-Zahra Palembang. It is hoped that this research will be useful for post partum mothers and can be applied at home so that the mother's breast milk production runs smoothly and the baby's nutrition is met.